Analysis of Phenolic Acids and Flavonoids in Rabbiteye Blueberry Leaves by UPLC-MS/MS and Preparation of Nanoemulsions and Extracts for Improving Antiaging Effects in Mice - Hsin-Rong Yu; Bing-Huei Chen (Foods, 2023)
Rabbiteye blueberry leaves, a waste produced after harvest of blueberry, are rich in polyphenols. This study aims to analyze phenolic acids and flavonoids in blueberry leaves by UPLC-MS/MS and prepare nanoemulsions for determining anti-aging activity in mice. Overall, 30% ethanol was the most suitable extraction solvent for total phenolic acids and total flavonoids. A total of four phenolic acids and four flavonoids were separated within seven minutes for further identification and quantitation by UPLC-MS/MS in selective reaction monitoring (SRM) mode, with 3-O-caffeoylquinic acid being present in the highest amount (6474.2 μg/g), followed by quercetin-3-O-galactoside (1943.9 μg/g), quercetin-3-O-rutinoside (1036.6 μg/g), quercetin-3-O-glucoside (867.2 μg/g), 5-O-caffeoylquinic acid (815.8 μg/g), kaempferol-3-O-glucoside (309.7 μg/g), 3,5-dicaffeoylquinic acid (195.3 μg/g), and 4,5-dicaffeoylquinic acid (60.8 μg/g). The blueberry nanoemulsion was prepared by using an appropriate ratio of soybean oil, Tween 80, glycerol, ethanol, and water at 1.2%, 8%, 2%, 2%, and 86.8%, respectively, and mixing with dried blueberry extract, with the mean particle size and zeta potential being 16 nm and −54 mV, respectively. A high stability was observed during storage of nanoemulsion for 90 days at 4 °C and heated at 100 °C for 2 h. An animal study revealed that this nanoemulsion could elevate dopamine content in mice brain as well as superoxide dismutase, glutathione peroxidase, and catalase activities in mice liver while reducing the contents of malondialdehyde and protein carbonyl in mice brains. Collectively, the high-dose nanoemulsion possessed the highest efficiency in improving mice aging with a promising potential for development into a health food.